Feasibility and importance of universal suicide screening in a pediatric emergency department - Steven C. Rogers; Shane J. Sacco; Kristen Volz; Danielle Chenard; Kevin Borrup; Kun Chen; Robert H. Aseltine (PLoS ONE, 2025)
Suicide is a leading cause of death in the United States. In 2018, the Joint Commission recommended screening patients for suicide risk in healthcare settings. Universal screening may increase the safety of at-risk youth, but is challenging for many pediatric emergency departments. We examined the feasibility and outcomes associated with universal suicide risk screening using a combination of two screening tools in a pediatric emergency department. This retrospective cohort study examined 10–18 year old patients presenting to a large, urban pediatric emergency department between September 2019 and August 2021. Key variables included patient demographic information, suicide risk screening results, and subsequent suicide attempts. There were 30,328 encounters in the pediatric emergency department over this two-year period. Screening was completed 84.8% of the time. Of the 17,332 unique patients screened, 83.9% were at minimal suicide risk, 7.0% low risk, 2.1% moderate risk, and 7.0% high risk. In the 6 months following screening, low-risk patients returning to the emergency department were 7.1 times likely to have a suicide attempt than minimal-risk patients, moderate-risk patients were 9.8 times likely, and high-risk patients were 15.5 times likely. Universal screening in a pediatric emergency department is feasible and informative. The combined screening tool protocol appeared to enhance efficiency while maintaining clinical accuracy. Universal screening identified a substantial proportion of pediatric emergency department patients at risk of subsequent suicide attempts, with the likelihood of a subsequent attempt strongly linked to increasing risk levels identified by screening.